2016
DOI: 10.3748/wjg.v22.i35.7983
|View full text |Cite
|
Sign up to set email alerts
|

Transanal surgery for obstructed defecation syndrome: Literature review and a single-center experience

Abstract: Obstructed defecation syndrome (ODS) is a functional disorder commonly encountered by colorectal surgeons and gastroenterologists, and greatly affects the quality of life of patients from both societal and psychological aspects. The underlying anatomical and pathophysiological changes of ODS are complex. However, intra-rectal intussusception and rectocele are frequently found in patients with ODS and both are thought to play an important role in the pathogenesis of ODS. With the development of evaluation metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…It is found that DF could be used as a much more accessible diagnostic method for patients with obstruction and an index combining DF and DRE can further assess for the screening and diagnosis of the cause(s) of their symptoms, to guide treatment in clinics [30]. The treatment of constipation includes drug therapy, anorectal myectomy, biofeedbac� or surgery, but in general these treat� ments have poor efficacy due to various etiology [31,32]. Thus treatment decisions should not depend solely on this type of feedbac�.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that DF could be used as a much more accessible diagnostic method for patients with obstruction and an index combining DF and DRE can further assess for the screening and diagnosis of the cause(s) of their symptoms, to guide treatment in clinics [30]. The treatment of constipation includes drug therapy, anorectal myectomy, biofeedbac� or surgery, but in general these treat� ments have poor efficacy due to various etiology [31,32]. Thus treatment decisions should not depend solely on this type of feedbac�.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it effectively rebuilds the rectal volume by resection of the prolapsed tissue. However, there is an ongoing debate between the supporters and the opponents of STARR as multiple postoperative complications have been reported[ 31 , 33 - 37 ] after STARR. Some long-term follow-up studies[ 11 , 38 ] revealed that the ODS score of patients who underwent the STARR procedure had a smooth increase after operation.…”
Section: Discussionmentioning
confidence: 99%
“…From June 2011 to June 2015, 41 (35 female) patients with a mean age ± SD of 62.3 ± 15.3 (range = 31-82) years underwent internal Delorme's procedure for rectocele and/ or internal rectal prolapse-induced ODS with impaired anal continence. Clinical assessment of constipation and incontinence was performed according to the Rome III criteria, 20 and all patients underwent surgical procedures only after experiencing failure of medical therapy. All candidates should have a complete diagnostic evaluation, including the following items, before undergoing the operation: (1) digital examination and anoscopy, (2) magnetic resonance defecography or enterocolpocystodefecography, (3) colonoscopy (patients with age ≥45 years or who have a familial history of colon cancer), (4) tridimensional 360° transanal ultrasonography, (5) anorectal manometry, and (6) neurophysiological tests (when indicated).…”
Section: Population and Preoperative Assessmentmentioning
confidence: 99%